Efficacy, safety and indirect comparisons of lasmiditan, rimegepant, and ubrogepant for the acute treatment of migraine: A systematic review and network meta-analysis of the literature. (March 2023) - Puledda, Francesca; Younis, Samaira; Huessler, Eva-Maria; Haghdoost, Faraidoon; Lisicki, Marco; Goadsby, Peter J; Tassorelli, Cristina
Background: We performed a random-effects network meta-analysis to study the efficacy and safety of newly developed drugs for the acute treatment of migraine attacks. Methods: MEDLINE via PubMed, Embase and The Cochrane Register of Controlled Trials were searched from inception to 11 February 2022. Phase 3 randomized controlled trials examining all formulations of lasmiditan, rimegepant and ubrogepant for the acute treatment of adults with migraine, were included. Data were extracted following the PRISMA guidelines. Results: Seven studies (SAMURAI, SPARTAN, CENTURION, Study 302, Study 303, ACHIEVE I and II) involving n  = 12, 859 patients were included. All treatments were superior in efficacy to placebo. Lasmiditan 200 mg showed the highest two-hour pain freedom, while two-hour freedom from most bothersome symptom was equally achieved by the higher doses of lasmiditan (100 and 200 mg), rimegepant and the higher doses of ubrogepant (50 and 100 mg). The odds of treatment-emergent adverse events were greatest with all doses of lasmiditan. Conclusion: Lasmiditan 200 mg was the most effective intervention in the treatment of migraine attacks, although it was associated with high degrees of dizziness, nausea and somnolence. Rimegepant showed slightly lower, but similar efficacy rates to lasmiditan. Ubrogepant had overall the best tolerability profile. These conclusions are limited by the absence of head-to-head comparisons, limitations of individual trials and of the meta-analysis methodology itself. PROSPERO trial registration: CRD42022308224